2020
DOI: 10.1039/c9ta14007g
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive enhancement of catalytic activity in Bi0.5Na0.5TiO3nanostructures: new insights into the design of efficient piezocatalysts and piezo-photocatalysts

Abstract: Bi0.5Na0.5TiO3 nanospheres show superior piezo-photocatalytic activity in water splitting, Cr(vi) reduction and degradation of organic pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…1 Over the past few years, typical piezoelectric nanomaterials have been exploited, including ZnO, Bi 4 Ti 3 O 12 , BaTiO 3 , Bi 0.5 Na 0.5 TiO 3 , C 3 N 4 , BN, WS 2 , and MoS 2 . [2][3][4][5][6][7][8][9][10] Among these materials, two-dimensional (2D) transition metal dichalcogenides (TMDs) have demonstrated excellent piezocatalytic performance in water splitting, contaminant degradation, carbon dioxide reduction, polymerization reaction and disease treatment due to their large piezoelectric coefficients, inherent layered crystal structures and high mechanical flexibility (that can withstand large strain). 11 However, their insufficient active sites and poor electrical conductivity hinder the improvement of their piezocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past few years, typical piezoelectric nanomaterials have been exploited, including ZnO, Bi 4 Ti 3 O 12 , BaTiO 3 , Bi 0.5 Na 0.5 TiO 3 , C 3 N 4 , BN, WS 2 , and MoS 2 . [2][3][4][5][6][7][8][9][10] Among these materials, two-dimensional (2D) transition metal dichalcogenides (TMDs) have demonstrated excellent piezocatalytic performance in water splitting, contaminant degradation, carbon dioxide reduction, polymerization reaction and disease treatment due to their large piezoelectric coefficients, inherent layered crystal structures and high mechanical flexibility (that can withstand large strain). 11 However, their insufficient active sites and poor electrical conductivity hinder the improvement of their piezocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Internal electric field causes the free electrons, and holes in BV readily move toward opposite polarity. 20,63,64 This suppresses the recombination possibility of electrons and holes causing more accumulation of free charge carriers at the BV surface. 65,66 The origin of the free charge carriers during ultrasonication remains open for discussion even now.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, electron transportation is also favored due to the possession of delocalized electrons on the - graphitic carbon network and higher conductivity of rGO [55]. In addition to these factors, it is also reported that the piezoelectric polarization field also provides further band bending [4,46].…”
Section: Fig 1 Xrd Patterns Of Bv Rgo 1rg-bv 2rg-bv 3rg-bv and 5rg-bv Powdersmentioning
confidence: 99%
“…The free electrons and holes within BiVO 4 get attracted, move in opposite direction towards the opposite polarity of the internal electric field. In this way, the recombination of free electrons and holes are inhibited, which results in more transportation of these free charge carriers to the BiVO 4 surface [46][47][48], which further participate in piezocatalytic surface reactions. Moreover, the piezoelectric polarization field also provides further band bending, which further assists in the easy transfer of free carriers to adsorbed pollutants undergoing piezocatalytic reactions [4,46,49].…”
Section: Fig 1 Xrd Patterns Of Bv Rgo 1rg-bv 2rg-bv 3rg-bv and 5rg-bv Powdersmentioning
confidence: 99%
See 1 more Smart Citation